The role of trade in adaptation to climate change - Gouel, Christophe; Laborde Debucquet, David (Centre For Economic Policy Research, 2019)
Given our collective failure to mitigate greenhouse gas emissions, the world will have to adapt to a certain level of climate change. This may mean that as climate change affects crops’ yield potential, new patterns of comparative advantage, and hence new trade flows, will emerge. This column examines the importance of the market adaptations in mediating welfare losses in the agricultural sector. The findings suggest a large role for international trade: when adjustments in trade flows are constrained, global welfare losses from climate change increase by 76%.